Characterization of substrates and inhibitors of the human heterodimeric transporter 4F2hc-LAT1 using purified protein and the scintillation proximity radioligand binding assay - Kantipudi, Satish; Harder, Daniel; Fotiadis, Dimitrios (Frontiers in Physiology, 2023)
Amino acids have diverse and essential roles in many cellular functions such as in protein synthesis, metabolism and as precursors of different hormones. Translocation of amino acids and derivatives thereof across biological membranes is mediated by amino acid transporters. 4F2hc-LAT1 is a heterodimeric amino acid transporter that is composed of two subunits belonging to the SLC3 (4F2hc) and SLC7 (LAT1) solute carrier families. The ancillary protein 4F2hc is responsible for the correct trafficking and regulation of the transporter LAT1. Preclinical studies have identified 4F2hc-LAT1 as a valid anticancer target due to its importance in tumor progression. The scintillation proximity assay (SPA) is a valuable radioligand binding assay that allows the identification and characterization of ligands of membrane proteins. Here, we present a SPA ligand binding study using purified recombinant human 4F2hc-LAT1 protein and the radioligand [3H]L-leucine as tracer. Binding affinities of different 4F2hc-LAT1 substrates and inhibitors determined by SPA are comparable with previously reported Km and IC50 values from 4F2hc-LAT1 cell-based uptake assays. In summary, the SPA is a valuable method for the identification and characterization of ligands of membrane transporters including inhibitors. In contrast to cell-based assays, where the potential interference with other proteins such as endogenous transporters persists, the SPA uses purified protein making target engagement and characterization of ligands highly reliable.